2014
DOI: 10.1158/1940-6207.capr-13-0359
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Criteria for the Identification of Lynch Syndrome among Unselected Patients with Endometrial Cancer

Abstract: Clinical criteria, primarily young age of cancer onset and family history of signature cancers, have been developed to identify individuals at elevated risk for Lynch Syndrome with the goals of early identification and cancer prevention. In 2007, the Society of Gynecologic Oncology (SGO) codified criteria for women presenting with gynecologic cancers. These criteria have not been validated in a population-based setting. For 412 unselected endometrial cancers, immunohistochemical expression of DNA mismatch repa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
13

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 42 publications
2
28
1
13
Order By: Relevance
“…24 A simplified cost-effectiveness analysis from a large retrospective cohort showed similar costs for universal testing versus triage using the SGO 5% to 10% risk-of criteria. 32 Prediction models support preselecting cases of EC using family pedigree criteria but not age cutoffs. 23 A prospective study of 179 women with EC revealed that 92% of suspected LS women received a diagnosis at older than 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…24 A simplified cost-effectiveness analysis from a large retrospective cohort showed similar costs for universal testing versus triage using the SGO 5% to 10% risk-of criteria. 32 Prediction models support preselecting cases of EC using family pedigree criteria but not age cutoffs. 23 A prospective study of 179 women with EC revealed that 92% of suspected LS women received a diagnosis at older than 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…For women with Lynch Syndrome, the lifetime risk of EC is 64%, and the lifetime risk of colorectal cancer is 54% (3). Prior studies have shown that use of clinical screening (patient age and family history of cancer) alone misses a substantial subset of endometrial cancer patients that may harbor a germline Lynch Syndrome mutation (4, 5). …”
Section: Introductionmentioning
confidence: 99%
“…Tumors with high levels of microsatellite instability (MSI-H) or immunohistochemical loss of expression of DNA MMR proteins in the absence of MLH1 gene methylation are suggestive of Lynch Syndrome. Many recently published studies have advocated for universal screening of endometrial carcinomas with MSI and/or IHC (4, 6, 7). The American College of Obstetricians and Gynecologists and the Society of Gynecologic Oncology have recently issued a practice bulletin recommending that universal tissue testing as a rational approach for identifying women at risk for Lynch-associated endometrial cancer (8).…”
Section: Introductionmentioning
confidence: 99%
“…14 A study performed by our group evaluated 412 sequential, unselected endometrial cancer patients, comparing SGO clinical screening criteria to universal tumor testing, and found the sensitivity and specificity for detecting tumors at elevated risk for Lynch Syndrome were 32.6% and 77%, respectively. 15 The clinically based screening criteria performed better at identifying women with increased risk for MLH1 and MSH2 mutations and performed poorly at identifying tumors with increased risk for MSH6 and PMS2 mutations. Other studies have also shown that individuals with germline mutations in MSH6 and PMS2 are more likely to have an older age at diagnosis and family histories that are dominated by gynecologic cancer or have less prevalent colon cancers.…”
Section: Screening Criteriamentioning
confidence: 99%
“…Other studies have also shown that individuals with germline mutations in MSH6 and PMS2 are more likely to have an older age at diagnosis and family histories that are dominated by gynecologic cancer or have less prevalent colon cancers. 1518 In addition to the limitations of these available screening criteria, patients with concerning family histories for Lynch Syndrome are not being universally screened by providers. 19 …”
Section: Screening Criteriamentioning
confidence: 99%